2017
DOI: 10.1136/vr.103948
|View full text |Cite
|
Sign up to set email alerts
|

Infectious keratoconjunctivitis and occurrence of Mycoplasma conjunctivae and Chlamydiaceae in small domestic ruminants from Central Karakoram, Pakistan

Abstract: Infectious keratoconjunctivitis (IKC) is a contagious eye disease primarily caused by Mycoplasma conjunctivae in domestic and wild Caprinae. Chlamydophila species have also been detected in ruminants with IKC. The objectives of this study are to investigate the ocular infection of M. conjunctivae and Chlamydiaceae and assess its interaction in relation to IKC in sheep and goats from remote communities around the Central Karakoram National Park in Pakistan, performing a combination of cross-sectional and case–c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 40 publications
2
18
1
Order By: Relevance
“…The higher prevalence of M. conjunctivae in younger Iberian ibexes during the IKC outbreak concurs with previous studies that reported higher M. conjunctivae prevalences in yearling ibexes (12) and lambs (39). A specific role of lambs for M. conjunctivae persistence in sheep flocks has also been suggested based on this higher prevalence and milder clinical signs (15,40).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The higher prevalence of M. conjunctivae in younger Iberian ibexes during the IKC outbreak concurs with previous studies that reported higher M. conjunctivae prevalences in yearling ibexes (12) and lambs (39). A specific role of lambs for M. conjunctivae persistence in sheep flocks has also been suggested based on this higher prevalence and milder clinical signs (15,40).…”
Section: Discussionsupporting
confidence: 78%
“…Given that mycoplasma virulence and clinical signs are positively related with transmission in ocular diseases (38), the high M. conjunctivae prevalence detected in 2014 was presumably achieved by chronic persistence in the eyes (15). Altogether, this suggests that M. conjunctivae probably became endemic in the Iberian ibex population with apparently low health implications, as typically reported in domestic sheep flocks (16,39).…”
Section: Discussionmentioning
confidence: 81%
“…Stresses such as dusty environmental conditions, transportation stress, bright sunlight and irritants are few predisposing factors for the disease. Besides, flies were found to serve as vectors for Mycoplasma spp Fernandez-Aguilar et al, 2017). Presumptive diagnosis of pinkeye is usually sufficient based on ocular sign and systemic infection.…”
Section: Introductionmentioning
confidence: 99%
“…Its detection in most of the sheep flocks sampled reinforce sheep as a proper host for the endemic M . conjunctivae maintenance [23,29]. Specific M .…”
Section: Discussionmentioning
confidence: 99%
“…Domestic Caprinae, i.e. sheep and goats, also undergo spontaneous IKC outbreaks, although in general the health impact is comparatively lower than in their wild counterparts [22,23]. …”
Section: Introductionmentioning
confidence: 99%